Exploring neural dysfunction in 'clinical high risk' for psychosis: A quantitative review of fMRI studies. (February 2015) - Dutt, Anirban; Tseng, Huai-Hsuan; Fonville, Leon; Drakesmith, Mark; Su, Liang; Evans, John; Zammit, Stanley; Jones, Derek; Lewis, Glyn; David, Anthony S.
Abstract: Individuals at clinical high risk (CHR) of developing psychosis present with widespread functional abnormalities in the brain. Cognitive deficits, including working memory (WM) problems, as commonly elicited by n-back tasks, are observed in CHR individuals. However, functional MRI (fMRI) studies, comprising a heterogeneous cluster of general and social cognition paradigms, have not necessarily demonstrated consistent and conclusive results in this population. Hence, a comprehensive review of fMRI studies, spanning almost one decade, was carried out to observe for general trends with respect to brain regions and cognitive systems most likely to be dysfunctional in CHR individuals. 32 studies were included for this review, out of which 22 met the criteria for quantitative analysis using activation likelihood estimation (ALE). Task related contrast activations were firstly analysed by comparing CHR and healthy control participants in the total pooled sample, followed by a comparison of general cognitive function studies (excluding social cognition paradigms), and finally by only looking at n-back working memory task based studies. Findings from the ALE implicated four key dysfunctional and distinct neural regions in the CHR group, namely the right inferior parietal lobule (rIPL), the left medial frontal gyrus (lmFG), the left superior temporal gyrus (lSTG) and the right fronto-polar cortex (rFPC) of the superior frontal gyrus (SFG). Narrowing down to relatively few significant dysfunctional neural regions is a step forward in reducing the apparent ambiguity of overall findings, which would help to target specific neural regions and pathways of interest for future research in CHR populations. Highlights: Widespread fMRI dysfunction is observed in clinical high risk (CHR) for psychosis. No consistent and conclusive evidence has emerged in fMRI literature in CHR. Most comprehensive review, spanning almost one decade in CHR carried out with ALE. Four dysfunctional regions spanning the frontal, parietal and temporal cortex found. Specific neural regions and pathways as potential targets for future research.